Post-Hysterectomy Transient Hydronephrosis: A Prospective Study - Mandana Mansour Ghanaie; Seyed Alaedin Asgari; Azar Haghbin; Fahime Mehdizade; Seyed Mohammad Asgari Ghalebin (Tehran University of Medical Sciences, 2021)
Objective: To determine the incidence and importance of transient asymptomatic hydronephrosis following total hysterectomy. Materials and methods: In a prospective study over 4 year, 368 women were studied who had undergone a total abdominal or vaginal hysterectomy. Totally, 95% of operations were done for benign diseases (abnormal uterine bleeding, chronic pelvic pain, uterine prolapse, etc.) and 5% were performed for uterine malignancy. Renal ultrasonography was performed before and 3, 7 and 28 days after the surgery for diagnosing hydronephrosis. Intravenous urography was performed in patients with either persistent/progressive or symptomatic hydronephrosis. Results: There was no intraoperative identifiable ureteral injury. Hydronephrosis was seen in 35 (9.5%), 21 (5.7%), and 1 (0.27%) patients at days 3, 7 and 28 after the operation, respectively. The degree of hydronephrosis was graded I, II or III. Considering the frequency and severity of hydronephrosis, the right kidney was affected more. Hydronephrosis correlated significantly with indication, duration and route of surgery as well as patient's age. All kidneys improved spontaneously, except one case which needed ureteral stenting with no surgical intervention (p=0.05). Conclusion: Transient hydronephrosis could occur after simple total hysterectomy despite the absence of any obvious intraoperative ureteral injury. It is noted in 9.5% of the patients within three days after the non-complicated surgery. The clinical course may be continued until one month.